(untitled) (Third Sector Social Economic Review, 2017)
Representation and arbitration are institutions that can be put into the Articles of Association under the voluntary provisions of the cooperatives law without any legal amendment. These institutions should be added / put into the type contracts prepared by the Ministry. Active cooperatives may apply this way by amending the articles of main contracts. Legislative changes are needed to overcome limitations and restrictions on general congressional votes. In this paper, ""representation and arbitration"" institutions were dealt with in order to make cooperatives sustainable and it was aimed to make the activities within cooperatives more functional and to make the relations between partners more efficient. If these two institutions, which are included in our legal system, will be placed and applied to main agreements of cooperatives: many problems within cooperatives will be reduced, as well as few remaining issues will be easily solved. A model proposal has been introduced in this regard.